Anatomy of A Hoax: A Network Analysis of Disinformation Propagation and Its Impact on Public Trust During Health Crises - Nyasha Zindove; Tendai Makoni; Chipo Mutema (Yayasan Adra Karima Hubbi, 2025)
Background. The rapid spread of disinformation during health crises has significant implications for public trust, especially when misinformation undermines health policies and safety measures. This research examines the anatomy of a disinformation hoax by analyzing the network dynamics of its propagation and the subsequent impact on public trust. The study focuses on the recent health crises, specifically during the COVID-19 pandemic, when false information about health measures, vaccines, and the virus itself circulated widely on social media platforms. Purpose. The primary objective of this research is to understand how disinformation networks form, spread, and influence public trust in health institutions and policies. Method. A network analysis approach was employed to map the flow of disinformation across social media platforms, identifying key nodes and influencers responsible for its spread. The study also incorporates survey data to measure the impact of exposure to disinformation on public trust. Results. Findings reveal that disinformation networks are highly interconnected, with certain individuals and groups acting as central nodes in the dissemination process. Moreover, exposure to disinformation significantly correlated with decreased trust in health authorities and the adoption of health measures. Conclusion. In conclusion, disinformation poses a serious threat to public trust during health crises, emphasizing the need for effective communication strategies and countermeasures to mitigate its impact.